2008
DOI: 10.1016/j.eurpsy.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Remission in the outpatient care of schizophrenia: 3-Year results from the Schizophrenia Outpatients Health Outcomes (SOHO) Study in France

Abstract: Remission can be achieved in a high proportion of patients. Factors such as being previously untreated, having paid employment and taking olanzapine are predictors of remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…Our sample was similar to those in other studies in terms of gender, employment rate (43,44), and marital status (5). However, the mean age of our patients was older compared with previous studies on patients with first-episode schizophrenia, indicating mean ages between 25 (1, 5) and 27 (6,7).…”
Section: Strengths and Limitationssupporting
confidence: 55%
“…Our sample was similar to those in other studies in terms of gender, employment rate (43,44), and marital status (5). However, the mean age of our patients was older compared with previous studies on patients with first-episode schizophrenia, indicating mean ages between 25 (1, 5) and 27 (6,7).…”
Section: Strengths and Limitationssupporting
confidence: 55%
“…A study in first-episode patients reported 52% SR over a 2-year follow-up [8]. Other studies even reported SR rates of 60% over 3 to 5-year periods [25][26][27] and of 66% over a 2-year period [28]. These discrepancies are likely to be related to the duration of follow-up, treatment history and patient characteristics.…”
Section: Symptomatic and Frmentioning
confidence: 99%
“…Several studies have been conducted to identify predictors of remission, and these can be summarized as follows: early treatment response; 52 remission status; 53 2 weeks of significant response to treatment; 54 a 20% symptom reduction at 2 weeks of treatment; 55 younger age, shorter duration of illness, shorter length of current episode, being employed, lower Positive and Negative Syndrome Scale (PANSS) general psychopathology and negative scales scores at baseline, and less suicidality; 43 educational status, subjective well-being, low score on the PANSS general psychopathology subscale, and side-effects; 56 early symptomatic and subjective well-being improvement 57 improvement at 2 weeks of 30% in the PANSS total score; 58 shorter duration of untreated psychosis (DUP); 44 , 59 , 60 better premorbid adjustment; 59 better functional level at baseline; 10 , 61 lower psychopathology or illness severity at baseline; 47 , 59 , 62 early symptomatic, functional, or quality of life improvement; 33 younger age, lower illness severity at baseline, better functioning level at baseline and early functional remission, early symptomatic, quality of life and medication adherence; 33 best premorbid social functioning, duration of psychotic symptoms before to study entry, diagnosis, percentage of time taking antipsychotic medication, global cognition score, and sex. 63 Predictors of remission can be considered relevant for the overall outcome of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%